CARCINOGENIC POLLUTANTS o-NITROANISOLE AND o-ANISIDINE ARE SUBSTRATES AND INDUCERS OF CYTOCHROMES P450 - Rydlova, Helena; Miksanova, Marketa; Ryslava, Helena; Stiborova, Marie (Biomedical papers, 2005)
2-Methoxyaniline (o-anisidine) and 2-methoxynitrobenzene (o-nitroanisole) are important pollutants and potent carcinogens for rodents. o-Anisidine is oxidized by microsomes of rats and rabbits to N-(2-methoxyphenyl)hydroxylamine that is also formed as the reduction metabolite of o-nitroanisole. o-Anisidine is a promiscuity substrate of rat and rabbit cytochrome P450 (CYP) enzymes, because CYPs of 1A, 2B, 2E and 3A subfamilies oxidize o-anisidine. Using purified CYP enzymes, reconstituted with NADPH: CYP reductase, rabbit CYP2E1 was the most efficient enzyme oxidizing o-anisidine, but the ability of CYP1A1, 1A2, 2B2, 2B4 and 3A6 to participate in o-anisidine oxidation was also proved. Utilizing Western blotting and consecutive immunoquantification employing chicken polyclonal anti bodies raised against various CYPs, the effect of o-anisidine and o-nitroanisole on the expression of the CYP enzymes was investigated. The expression of CYP1A1/2 was found to be strongly induced in rats treated with either compounds. In addition, 7-ethoxyresorufin O-deethylation, a marker activity for both CYP1A1 and 1A2, was significantly increased in rats treated with either carcinogen. The data demonstrate the participation of different rat and rabbit CYP enzymes in o-anisidine oxidation and indicate that both experimental animal species might serve as suitable models to mimic the o-anisidine oxidation in human. Furthermore, by induction of rat hepatic and renal CYP1A1/2, both o-nitroanisole and o-anisidine influence their carcinogenic effects, modifying their detoxification and/or activation pathways.
Keywords: o-Nitroanisole/o-Anisidine/Carcinogen/Cytochromes P450/Induction